Analisis Potensi Penggunaan Moda Transportasi Tidak Bermotor Pada Mahasiswa di Kampus Terpadu Universitas Islam Indonesia - Prayitno, Prayogo Afang; Kemal Fardianto; Faza Fawzan Bastarianto; Muhammad Kennyzyra Bintang; Raihan Pasha Isheka (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2023)
The large number of students is directly proportional to the increase in private vehicles on campus, resulting in traffic congestion. Efforts should be made to encourage motorized vehicle users to switch to sustainable modes of transportation. This study aims to determine student dependence on motorized vehicles to go to campus and identify factors associated with using sustainable modes of transportation at the Universitas Islam Indonesia (UII). The data sample consisted of 614 respondents, collected through online simple random sampling. The collected data were then analyzed using the Chi-Square test. The survey data reveals a significant reliance on motorized vehicles to get to campus, with 67% of trips within a 2-kilometer radius made by motor vehicles. Based on the Chi-Square test results, factors such as motor vehicle ownership, driving license ownership, travel distance, and the primary mode of transportation are strongly associatedwith the willingness to walk or cycle. This condition indicates that practicality or habitual aspects have a stronger relationship with students' willingness to use sustainable transportation than demographic or socioeconomic factors. Thus, efforts are needed to increase the practicality of using sustainable transportation to optimize sustainable campus development.